2007
DOI: 10.1159/000102277
|View full text |Cite
|
Sign up to set email alerts
|

Arterial Vimentin Is a Transglutaminase Substrate: A Link between Vasomotor Activity and Remodeling?

Abstract: Background/Aims: The transglutaminases (TG2 and factor XIIIa) may contribute to the stability of arteries by cross-linking a variety of substrates, including extracellular matrix proteins and protease inhibitors. The preferred substrates have never been determined, however. Methods: We used an amine donor, 5-biotinamidopentylamine, that is covalently linked to acceptor glutamine residues, to determine transglutaminase substrates in carotid endarterectomy tissue. Results: The incorporation of 5-biotinamidopenty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 58 publications
(38 reference statements)
3
15
0
Order By: Relevance
“…Indeed, we observed complete dilatation upon inhibition of Tgase activity in isolated coronary arteries [12]. Others identified vimentin as a major substrate for type 2 Tgase in vascular tissue, and suggested that vimentin links Tgases to vasomotor activity and remodeling [60]. …”
Section: Small Artery Remodelingmentioning
confidence: 76%
“…Indeed, we observed complete dilatation upon inhibition of Tgase activity in isolated coronary arteries [12]. Others identified vimentin as a major substrate for type 2 Tgase in vascular tissue, and suggested that vimentin links Tgases to vasomotor activity and remodeling [60]. …”
Section: Small Artery Remodelingmentioning
confidence: 76%
“…Previous data have indicated differences in TGF␤ signaling pathway between BAV and TAV patients (4,26). Furthermore, vimentin (VIM), one of the components of intermediate filament, is a major substrate for transglutaminases (27). Hence, medial degeneration in TAV patients may be the result of vimentin crosslinking by TGM2, as has been proposed for arterial remodeling (27).…”
Section: Discussionmentioning
confidence: 95%
“…Furthermore, vimentin (VIM), one of the components of intermediate filament, is a major substrate for transglutaminases (27). Hence, medial degeneration in TAV patients may be the result of vimentin crosslinking by TGM2, as has been proposed for arterial remodeling (27). Moreover, most of the proteins specifically associated with dilatation in TAV i.e.…”
Section: Discussionmentioning
confidence: 99%
“…TG2 is thought to play a role in cytoskeleton organisation, since β-actin, α-actinin, tubulin, cofilin and vimentin are all TG2 substrates. [28][29][30][31] Three protein chaperones, B23, Hsp60 and mortalin (heat shock 70 kDa protein 9) were all under-represented in the cytoskeleton fraction of SW480/lamA cells. All three proteins have been implicated in cancer progression [32][33][34] and all three bind to cytoskeleton proteins and influence cytoskeleton dynamics and organisation.…”
Section: Discussionmentioning
confidence: 99%